Effect of time step interval and time integration schemes in Pseudo-Dynamic analysis - Ozturk, Sezer; Doran, Bilge; Aksoylar, Cenk (ELSEVIER SCIENCE INC, 2023)
Pseudo Dynamic Analysis technique is an alternative method for exploring structural performance by combining analytical and experimental investigation. Compared to shake table tests, it is a more economical method, and its reliability has been proven over many years of the studies. The damage occurrence and process can be monitored on the test sample due to experiments performed at low speeds. In this study, the behaviour of a single degree of freedom, cantilever column system, under the effect of the pulse load and earthquake record was investigated both numerically and experimentally using Pseudo Dynamic Analysis method. The effects of two different time integration schemes and various time step interval values on analyses were examined in the investigations and the results were compared. Numerical analyses were performed by alpha-operator splitting method and central differences method, and experimental studies were performed by alpha-operator splitting method. In experimental investigations, approximate results were obtained with numerical studies for certain values of the time step. At small time interval values, experimental results deteriorated. It is purposed to determine the optimum time step interval value that can be utilised in the Pseudo Dynamic Test method.
Keywords: Pseudo dynamic simulation; Steel structures; Experimental investigation; Numerical study; SEISMIC PERFORMANCE; Engineering